Postoperative follow-up programs improve survival in curatively resected gastric and junctional cancer patients: a propensity score matched analysis - Peters, Leila; Strowitzki, Moritz; Blank, Susanne; Nienhüser, Henrik; Dorr, Sara; Haag, Georg Martin; Jäger, Dirk; Ott, Katja; Büchler, Markus W.; Ulrich, Alexis; Schmidt, Thomas (Gastric cancer, 2018)
BACKGROUND: To date there is no evidence that more intensive follow-up after surgery for esophagogastric adenocarcinoma translates into improved survival. This study aimed to evaluate the impact of standardized surveillance by a specialized center after resection on survival. - METHODS: Data of 587 patients were analyzed who underwent curative surgery for esophagogastric adenocarcinoma in our institution. Based on their postoperative surveillance, patients were assigned to either standardized follow-up (SFU) by the National Center for Tumor Diseases (SFU group) or individual follow-up by other physicians (non-SFU group). Propensity score matching (PSM) was performed to compensate for heterogeneity between groups. Groups were compared regarding clinicopathological findings, recurrence, and impact on survival before and after PSM. - RESULTS: Of 587 patients, 32.7% were in the SFU and 67.3% in the non-SFU group. Recurrence occurred in 39.4% of patients and 92.6% within the first 3 years; 73.6% were treated, and of those 17.1% underwent resection. In recurrent patients overall and post-recurrence survival (OS/PRS) was influenced by diagnostic tools (p < 0.05), treatment (p ≤ 0.001), and resection of recurrence (p ≤ 0.001). Standardized follow-up significantly improved OS (84.9 vs. 38.4 months, p = 0.040) in matched analysis and was an independent positive predictor of OS before and after PSM (p = 0.034/0.013, respectively). - CONCLUSION: After PSM, standardized follow-up by a specialized center significantly improved OS. Cross-sectional imaging and treatment of recurrence were associated with better outcome. Regular follow-up by cross-sectional imaging especially during the first 3 years should be recommended by national guidelines, since early detection might help select patients for treatment of recurrence and even resection in few designated cases.